Emotion and Aging: Recent Evidence from Brain and Behavior - Natalie Ebner (Frontiers Research Topics, 2015)
Emotions play a central role in every human life, from the moment we are born until we die. They prepare the body for action, guide decisions, and highlight what should be noticed and remembered. Since emotions are central to daily functioning and well-being, it is important to understand the extent to which aging affects the perception of, attention to, memory for, as well as experience and regulation of emotions. An early scientific view of how people's emotions are affected by aging argued that aging led to a deterioration of emotional function. This theory, represented by for example Carl Jung (1875-1961), claimed that old age is a period of life when people feel an increased emotional sameness and less emotional energy. According to this scientific view, the aging emotional landscape was bleached, barren, and flattened. Current psychological research, however, shows that emotion is rather a psychological domain that is relatively unaffected by the aging process or even improves with age, in contrast to most cognitive functions. For example, even though there is evidence that aging is associated with deficits in emotion recognition, various emotional functions seem to remain intact or become better with age, such as the ability to regulate one's emotions or the extent of experiencing positive emotions. However, more research is needed to determine brain and behavior related, quantitative and qualitative age-related changes of different aspects of emotion processing and emotional functioning. In the current Frontiers research topic we aim to present exciting new findings related to the effects of healthy aging on both more perceptually driven bottom-up as well as more cognitively driven top-down aspects of emotions. In particular, questions such as the following need to be raised and addressed: What neural and behavioral processes are underlying age differences in emotion perception and memory for emotional information? Are there differences between how older and younger adults experience and regulate their emotions, and what drives these differences? Is there a gradual reduction or more of a qualitative change of our emotional experiences over the life cycle, from the turbulent childhood and youth to the mellower old age? And what aspects of age-related changes in emotional processing can be explained by age-related changes in the brain, and which are more affected by other factors such as changes in other body systems, in experiential processes, or in overall life goals?